Effect of thermal treatment on properties and microstructures of porous alumina - Abd Rahman , Hamimah (2010)
This paper investigates influence of thermal treatment on the microstructure and properties of porous alumina-starch ceramics. The porous bodies were prepared through polymeric sponge method. The dried slurry of alumina and starch mixture was crushed and sieved on a 63 μm screen. The undersize particles were pre-sintered in the powder form at 1100, 1200, 1300, 1400 and 1500°C for 2 hours in an air furnace. The pressed forms of ceramic powder then sintered at 1500°C to produce porous alumina ceramic bodies with porosity from 25.9 to 31.2%. The modulus of rupture has successfully been improved about five times higher compared to the strength of porous ceramic body without presintering process. Besides that, the hardness value for double sintered porous ceramic was increased to 35.90 HV. SEM micrographs revealed better microstructural features of the ceramic body produced from pre-sintered samples. Based on the results obtained, pre-sintered process in the preparation of alumina-starch porous ceramics has managed to improve the hardness and strength of porous ceramic significantly. These ceramic bodies may